Pelaksanaan Tugas Disperindag Dalam Melakukan Pengawasan Minuman Beralkohol Berdasarkan Perda Kota Kupang Nomor 12 Tahun 2016 - Nafie, Indra Apriliando; Yohanes, Saryono; Ratu Udju, Hernimus (Law Faculty, Nusa Cendana University, 2024)
In the current era, cases are increasing due to consuming alcoholic drinks, both in the community and among teenagers, one of which is in the city of Kupang. So the Kupang city government must handle cases of free distribution of alcoholic drinks among the public, one of which is by giving the Kupang city government duties and responsibilities to the Department of Industry and Trade. This research aims to determine the duties and responsibilities of the industry and trade department in supervising alcoholic beverages, and the obstacles that exist in supervising alcoholic beverages. The type or types of research used in this research proposal is empirical juridical research, namely research carried out by going directly into the research field to collect information as a required legal fact, using an interview approach from the required sources. The research results found that before the supervision was carried out, the Department of Industry and Trade formed a supervision team, place and time for supervision, checked the completeness of business permits, carried out an assessment, and ultimately imposed sanctions on those who violated them. and Obstacles: lack of community cooperation in government efforts and lack of strict sanctions given to sellers, which only take the form of warnings. The proposed lack of outreach by the Department of Industry and Trade in conducting outreach to sub-districts in Kupang City regarding the sale of alcoholic drinks to the public, business actors should comply with existing regulations.